2015
DOI: 10.1016/j.eurpsy.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of coping and self-esteem on the relationship between defeat, entrapment and suicidality in a sample of prisoners at high risk of suicide

Abstract: Background-Research is sparse which examines pathways to suicide, and resilience to suicide, in people who are particularly vulnerable to suicide, for example, prison inmates. The purpose of this study was to examine the ways in which perceptions of self-esteem and coping ability interacted with defeat and entrapment to both amplify suicidal thoughts and feelings, and to act as a buffer against suicidal thoughts and feelings.Methods-Participants were 65 male prisoners at high risk of suicide. A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 45 publications
0
43
0
1
Order By: Relevance
“…Recent evidence indicates that being higher on such resilience constructs is associated with lower suicide ideation and behavior (Bezdjian, Burchett, Schneider, Baker, & Garb, ; Dhingra, Boduszek, & O'Connor, ). Although there is some debate around how resilience is operationalized (Bonanno, ), a body of literature suggests that resilience is a pervasive construct, and it moderates both defeat and entrapment's relationship with established risk factors such as hopelessness (Gooding et al., ). Therefore, in the context of the motivational phase of the IMV model, we propose that a resilience construct that taps directly into the ability to bounce back or recover from stress would moderate the transition from defeat to entrapment (i.e., a threat to self‐moderator ) and from entrapment to suicide ideation (i.e., a motivational moderator ).…”
Section: Integrated Motivational–volitional Model Of Suicidal Behaviormentioning
confidence: 99%
“…Recent evidence indicates that being higher on such resilience constructs is associated with lower suicide ideation and behavior (Bezdjian, Burchett, Schneider, Baker, & Garb, ; Dhingra, Boduszek, & O'Connor, ). Although there is some debate around how resilience is operationalized (Bonanno, ), a body of literature suggests that resilience is a pervasive construct, and it moderates both defeat and entrapment's relationship with established risk factors such as hopelessness (Gooding et al., ). Therefore, in the context of the motivational phase of the IMV model, we propose that a resilience construct that taps directly into the ability to bounce back or recover from stress would moderate the transition from defeat to entrapment (i.e., a threat to self‐moderator ) and from entrapment to suicide ideation (i.e., a motivational moderator ).…”
Section: Integrated Motivational–volitional Model Of Suicidal Behaviormentioning
confidence: 99%
“…However, as has been pointed out by Johnson et al (), factors that are negatively associated with suicide ideation—even over longer time—will not necessarily have a buffering impact on risk, and factors that have no linear association with suicide ideation may still moderate the impact of risk (cf. Gooding et al, ). Therefore, a more stringent evaluation of the buffering qualities of the abovementioned constructs is needed—especially because little is known about the relative importance of different resilience constructs, in moderating the association between depression—as a strong and prevalent risk factor—and suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…However, as has been pointed out by Johnson et al (2011), factors that are negatively associated with suicide ideation-even over longer time-will not necessarily have a buffering impact on risk, and factors that have no linear association with suicide ideation may still moderate the impact of risk (cf. Gooding et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, feelings of entrapment and desire to escape have also been strongly linked to suicide ideation [8][9][10][11]. The Cry of Pain Model suggested that in a sample of rst-time and repeat self-harm patients, entrapment had a mediating role in the defeat-suicidal ideation relationship [12].…”
Section: Introductionmentioning
confidence: 99%